A Case Study: Active Learning Approaches to Improve Learning in Electrical Network - Sharma, Megha (Journal of Engineering Education Transformations, 2018)
Active learning approach in teaching learning process is quite useful and beneficial. It provides depth knowledge of content and active involvement in the class. Surveys and studies in the field of educational technology have proved this. Many educational institutes like IITs and NITs and Engineering colleges are adopting active learning approaches for making their teaching learning methods better. In active learning teacher acts as facilitators rather than one-way suppliers of information. In this paper teacher has tried to prove that in her subject Electrical Network by using active learning techniques students have performed better and learnt more.This has been proved by showing the results of two consecutive years.